1997
DOI: 10.1007/s001250050785
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of glomerular gelatinase B (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in obese Zucker rats

Abstract: The obese Zucker rat is an autosomal recessive model of obesity and hyperlipidaemia with many similarities to human non-insulin-dependent diabetes mellitus (NIDDM) [1][2][3]. These metabolic abnormalities precede the development of albuminuria and mesangial matrix expansion followed by segmental glomerulosclerosis [4,5]. Accumulation of matrix components within the mesangium has been demonstrated for collagen IV, fibronectin, laminin and proteoglycans [6][7][8].The turnover of extracellular matrix is dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
(44 reference statements)
4
22
0
1
Order By: Relevance
“…Although not reaching statistical significance, pair-feeding also reduced expression of fibronectin (expressed in states of mesangial expansion, such as early in glomerulosclerosis) and the 92-kDa collagenase (e.g., MMP-9, Gelatinase B, up-regulated in developing glomerular disease, when collagen IV is being actively synthesized and turned over). Each of these has been implicated in glomerular disease associated with hyperlipidemia in rat models (13)(14)(15)(16). Statistical significance was not reached in the latter two genes, primarily due to the relatively heterogeneous gene expression observed in AL obese rats in this and other reports (6,17).…”
Section: Glomerular Gene Expressionmentioning
confidence: 58%
“…Although not reaching statistical significance, pair-feeding also reduced expression of fibronectin (expressed in states of mesangial expansion, such as early in glomerulosclerosis) and the 92-kDa collagenase (e.g., MMP-9, Gelatinase B, up-regulated in developing glomerular disease, when collagen IV is being actively synthesized and turned over). Each of these has been implicated in glomerular disease associated with hyperlipidemia in rat models (13)(14)(15)(16). Statistical significance was not reached in the latter two genes, primarily due to the relatively heterogeneous gene expression observed in AL obese rats in this and other reports (6,17).…”
Section: Glomerular Gene Expressionmentioning
confidence: 58%
“…Marked decreases in MMP-9 mRNA expression and enzymatic activity were also noted in the glomeruli of diabetic obese Zucker rats (31). We observed that baseline MMP-9 expression and activity were markedly decreased in MC after long-term exposure to high ambient glucose levels (32,33).…”
mentioning
confidence: 53%
“…MMP-2 is predominantly inhibited by TIMP-2 17 and TIMP-4, 18 while MMP-9 is inhibited mainly by TIMP-1. 19 An imbalance between MMPs and TIMPs expression was shown in recent studies to be connected with a variety of different tumours, for example, lung, 20 colon, 21 breast 22 and prostate. 23 In the present study, the expression of MMP-2 and -9, and TIMP-1 and -2 in prostate cancer tissue was examined using immunohistochemical methods.…”
Section: Introductionmentioning
confidence: 99%